Impact of an extended audit on identifying heart failure patients in general practice: baseline results of the OSCAR‐HF pilot study. (24th September 2020) - Smeets, Miek; Vaes, Bert; Aertgeerts, Bert; Raat, Willem; Penders, Joris; Vercammen, Jan; Droogne, Walter; Mullens, Wilfried; Janssens, Stefan
Abstract: Aims: Identifying heart failure (HF) patients in general practice is challenging, and little is known about the current quality of care. We implemented an extended audit from the electronic health records (EHRs) of general practitioners (GPs) to identify HF patients and investigate patient characteristics and quality of care. Methods and results: This study describes the baseline results of the OSCAR‐HF pilot study in eight general practices (51 GPs) in Flanders, Belgium. This prospective trial ran for 6 months. Interventions included an extended audit, an N‐terminal pro‐B‐type natriuretic peptide point‐of‐care test, and assistance of a specialist HF nurse. The extended audit searched on risk factors for HF, HF symptoms, signs, and medication in the GPs' EHR to generate a list of possible HF patients. GPs determined which patients had HF. Those HF patients constituted the OSCAR‐HF study population. Each patient file was manually revised to extract biomarker measurements, echocardiography data, and quality indicators. An independent panel of experts assessed the validity of GPs' HF diagnoses. Feedback about the validity of the HF diagnosis was given to the GP. Out of 18 011 patients ≥ 40 years, we identified 310 patients with a registered HF diagnosis before the study start (HF prevalence: 1.7%). The extended audit led to a 74% increase in identified HF patients ( n  = 538, HF prevalence: 3.0%) with a mean age of 79 ± 11 years. The prevalence of HF with reduced ejection fraction (HFrEF) was 20% ( n  = 110). A high proportion of patients underwent echocardiography in the past 5 years (86%, n  = 462). Natriuretic peptides were rarely available in patients' files (19%, n  = 100). Medical specialists should improve communication about the HF diagnosis because a specialist diagnosis was present in only 225 patients (42%) while 67% ( n  = 359) of the HF diagnoses were judged objectified by a panel of experts. Assigning a diagnosis of HF was particularly difficult in HF patients with preserved EF (HFpEF). HFrEF treatment rates with renin–angiotensin–aldosterone system blockers (84%, n  = 92) and beta‐blockers (86%, n  = 94) were very good; however, target doses were hardly reached (34% and 14%, respectively). Conclusions: This study highlighted the need to improve case finding for HF in general practice and showed that an extended audit in the GPs' EHR was a successful strategy to do so. To improve the quality of HF care in general practice, specific strategies are needed to diagnose HFpEF and to reach target doses of disease‐modifying drugs in HFrEF patients.